Types of cultural palimpsest landscapes in the Mediterranean basin delimitation and mapping - Oxana A. Klimanova; Eugeny Yu. Kolbowsky (European Journal of Geography)
Cultural heritage sites in the Mediterranean basin reflect long–term cultural and land-use changes associated with different regional civilizations. We integrated data on historical heritage sites and civilization areas using GIS-mapping and modeling. Analysis of the World Heritage Database allows classifying 190 sites into eight cultural landscape categories – rock paintings, remnants of ancient settlements, architecture monuments, monasteries/castles, temples/necropolis, historical city centers, nature management systems, cultural landscapes, and defining eight civilization époques – prehistorical, ancient, antique, early medieval, late medieval, modern age, and recent. Each type of civilization change corresponds to a territory where cultural landscapes of various eras are superimposed to form a landscape palimpsest, including two- and three-layer systems formed under the impact of two or three civilizations. The resulting map and data are useful for comparative studies focusing on the relationship between the length of historical records and the “civilization” time-scale in which past cultural landscapes existed.